Gambaran Perilaku Santri Putri Terhadap Menstrual Hygiene - Lestari, Resti Dharma; Ermiati, Lilis Mamuroh; Ermiati, Ermiati; Srimurni, Nita Ayu (Journal of Maternity Care and Reproductive Health, 2025)
Menstrual hygiene is an essential aspect of maintaining the reproductive health of adolescent girls. However, a lack of awareness and limited access to sanitation facilities can increase the risk of reproductive tract infections. This study aims to describe the menstrual hygiene behavior of female students at Pondok Pesantren Raudlatul Mutaalimin Garut and identify areas that need improvement. This research used a descriptive quantitative design with a total sampling technique, involving 65 female students. Data were collected through a questionnaire covering aspects such as handwashing, bathing, sanitary pad usage, genital hygiene, physical activity, and nutritious food consumption. The data were analyzed using univariate analysis and presented in frequency distribution tables. The results showed that most students demonstrated good menstrual hygiene behavior, particularly in handwashing (93.8%), genital hygiene (89.2%), and regular bathing (81.5%). However, less optimal practices were found in proper sanitary pad usage (21.5%) and nutritious food consumption (41.5%). While most students practiced good menstrual hygiene, further education is needed to improve their understanding of proper sanitary pad usage and the importance of consuming nutritious food during menstruation to support optimal reproductive health. Further research is suggested to focus on the factors causing bad behavior and the development of educational interventions to improve menstrual hygiene of students.Keywords: Menstrual hygiene, behavior, adolescent girls, female students.